Différence des corps, égalité des droits : le sport et la reconnaissance des « races de couleur » (États-Unis, Caraïbes, v. 1850-v. 1950) - Nicolas Martin-Breteau (Centre de Recherches sur les Mondes Américains, 2013)
This article seeks to study how African Americans countered the discourse on the “natural” superiority of white humanity between the mid-19th and the mid-20th centuries. Since racism toward Africans Americans was legitimated by their blackness, they set up perfectionist strategies of “racial uplift” whose goal was the public presentation of the dignity of the black body. By so doing, they hoped to gain symbolic recognition and civic equality with their white fellow citizens. Thus, we shall study how middle- and upper-class black people in the United States used sport as a performative means for uplifting individuals' bodies and achieving collective emancipation. This tactic sought to prove the identity between black and white people—their shared humanity—to obtain the right to get rights, that is, to integrate the realms of the American democracy as full citizens. Based on the conclusions of this first analysis, hypotheses shall be outlined about the bodily political strategies of other “colored” populations of America, such as American-Indians and the black populations of the Caribbean.